Identification of counselor mind process on online counseling - M. Ramli; Husni Hanafi; Nur Hidayah; Adi Atmoko; Fifi Khoirul Fitriyah (Institute of Advanced Engineering and Science, 2023)
The internal counselor competence refers to the metacognition skills to manage all their mental experiences and internal conditions. These are in the form of Mind skills. In particular, in the industrial revolution 4.0 and the covid-19 pandemic situation, online counselors face many unpredictable and unfamiliar conditions. This study aims to identify the state of level the counselor's mind skills during online counseling sessions. This research method uses survey research methods of 181 online counselors in various regions in Indonesia. Mind Skills Journal is the instrument used for data collection to assess the four levels of counselor metacognition (Reflective, Strategic, Aware, and Tacit). The analysis used basic statistics and graphs. The results showed the overall score of the Mind skills level was 78.166%, which was in the Strategic Use level. The Mind skills contribution can be counselor self-regulation, counselor assessment, verbalization, information visualization description, causal analysis, and predictive planning. Suggestions based on research results are the need for an alternative to improve mind skills through reflective learning of prospective counselors and reflective supervision activities of counselors in the field.